Learning curves for transfemoral transcatheter aortic valve replacement in the PARTNER‐I trial: Technical performance. Issue 1 (10th August 2015) - Alli, Oluseun; Rihal, Charanjit S.; Suri, Rakesh M.; Greason, Kevin L.; Waksman, Ron; Minha, Sa'ar; Torguson, Rebecca; Pichard, Augusto D.; Mack, Michael; Svensson, Lars G.; Rajeswaran, Jeevanantham; Lowry, Ashley M.; et al.
Abstract : Objectives: To assess technical performance learning curves of teams performing transfemoral transcatheter aortic valve replacement (TF‐TAVR). Background: TF‐TAVR is a new procedure for treating severe aortic stenosis. The number of cases required for procedural efficiency is unknown. Methods: In the PARTNER‐I trial, 1, 521 patients underwent TF‐TAVR from 4/2007–2/2012. Learning curve analysis of technical performance metrics was performed using institution‐specific patient sequence number, interval between procedures, and institutional trial entry date. Learning curve characteristics were assessed using semi‐parametric and parametric mixed‐effects models. Results: As patient sequence number increased, average procedure time decreased from 154 to 85 minutes ( P < 0.0001), and fluoroscopy time from 28 to 20 minutes ( P < 0.0001). Procedure time plateaued at an average of 83 minutes (range 52–140). Procedure time plateau was dynamic during the course of the trial, averaging 25 cases (range 21–52) by its end. The later institutions enrolled in the trial, the shorter the initial procedure time. During the trial, percutaneous rather than surgical access increased from 7.9% to 69%. Conclusions: Technical performance learning curves exist for TF‐TAVR; procedural efficiency increased with experience, with concomitant decreases in radiation and contrast media exposure. The number of cases needed to achieve efficiency decreased progressively, with optimal procedural performance reached after approximately 25 cases for late‐entering institutions. Knowledge and experience accumulated by early TF‐TAVR institutions were disseminated, shortening the learning curve of late‐entering institutions. Technological advances resulting from learning during the trial moved the field from initial conservative surgical cut‐down to percutaneous access for most patients. © 2015 Wiley Periodicals, Inc.